The Relationship between Maternal Media Literacy and Children's Media Literacy - Saeedfar, Parisa; Hejazi, Seyed Naser; Behyan, Shapour (Psychology of Woman Journal, 2023)
Objective: Since children and adolescents are one of the most important consumers of media and media play a significant role in shaping and influencing their behavior towards consumption patterns and daily life activities, this study aimed to elucidate the role of maternal media literacy in children's media literacy.Methods and Materials: The present research adopted a descriptive correlational design. The population consisted of all male and female students attending public secondary schools in District 5 of Tehran city and engaged in studies during the academic year of 2022-2023. The sample size, determined using Morgan and Krejcie table, was 249 individuals, selected through multi-stage cluster sampling method. To measure the research variables, the Toman Media Literacy Questionnaire (1995) and a researcher-made questionnaire on media literacy competence were employed.Findings: Content validity of the questionnaires was confirmed by experts, and their reliability was estimated using Cronbach's alpha coefficient, yielding 0.82 and 0.83, respectively. The results obtained from the structural equation modeling using PLS3 software indicated that children's media literacy can be predicted based on maternal media literacy (p > 0.01).Conclusion: Considering the role of maternal media literacy in enhancing children's media literacy competence, it can be inferred that maternal media literacy has had a significant influence on the media literacy competence of adolescent students.